Angiotensin-converting enzyme inhibitor-induced angioedema may not be a class-related event - Hassan A Farhat (Journal of Emergency Medicine, Trauma and Acute Care, 2012)
Angioedema is a rare but potentially life threatening condition commonly associated with angiotensin-converting enzyme inhibitors (ACEIs). The incidence is approximately 0.1- 0.2% and may occur within the first week to several years of taking an ACEI. We present a case of a 37-year-old African-American male who was uneventfully taking a drug combination of quinapril and hydrochlorothiazide. When his medication was changed to lisinopril he developed an acute swelling of his lower lip and chin on fifth dose. The angioedema subsided within 24 hours after discontinuation of lisinopril. Therefore, this suggests that future treatment with ACEIs, as well as angiotensin receptor blockers (ARBs), is not recommended in this type of patient.